(untitled) (Western European Journal of Linguistics and Education, 2025)
the article offers a thorough approach intended to provide pupils the ability to independently find and choose educational materials. The methodology seeks to improve students’ capacity to traverse the constantly growing virtual world of information by applying a systematic framework that incorporates critical thinking, online research techniques, and source assessment. Instructors may better create an autonomous learning environment where students can become critical information pickers by using practice-based methodologies and real-world examples.